2020
DOI: 10.3390/nu12082420
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Consumption of Alcohol on Intraocular Pressure: Korea National Health and Nutrition Examination Survey 2010 to 2011

Abstract: This study researched the association between alcohol consumption, intraocular pressure (IOP), and risk of open-angle glaucoma (OAG) using nationwide population-based cross-sectional data from the Korean population based survey. Information on alcohol intake was obtained by questionnaire and comprehensive ophthalmic examinations were performed. Among a total of 6057 participants, the prevalence of OAG was 4.4% (6.0% for men and 3.0% for women). Multivariate adjusted models showed that alcohol consumption showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…A further 2 studies found positive linear associations between alcohol intake and IOP in men, but not women, without glaucoma (IOP difference of 0.7–1.4 mmHg between highest intake group and no intake group). 18 , 20 In one of these studies, consumption of alcohol > 4 times/week in women with glaucoma was associated with higher IOP (+2.8 mmHg) compared with nondrinkers, but with no evidence of linear trend. 18 Alcohol intake was not associated with IOP in 1 study 52 and negatively associated (IOP difference <0.1 mmHg) in previous, but not current, drinkers in another.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A further 2 studies found positive linear associations between alcohol intake and IOP in men, but not women, without glaucoma (IOP difference of 0.7–1.4 mmHg between highest intake group and no intake group). 18 , 20 In one of these studies, consumption of alcohol > 4 times/week in women with glaucoma was associated with higher IOP (+2.8 mmHg) compared with nondrinkers, but with no evidence of linear trend. 18 Alcohol intake was not associated with IOP in 1 study 52 and negatively associated (IOP difference <0.1 mmHg) in previous, but not current, drinkers in another.…”
Section: Resultsmentioning
confidence: 99%
“…Ocular hypertension was defined as IOP > 21 mmHg with no features of glaucomatous optic neuropathy by all studies using this as an outcome measure. Intraocular pressure was measured by applanation tonometry in 7 studies 16 , 18 , 19 , 21 , 22 , 52 and noncontact tonometry in 3 studies. 17 , 20 , 53 All studies limited their analyses to participants without glaucoma or stratified outcomes by glaucoma status.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol consumption is often considered detrimental to glaucoma patients. Yet, reports on the direct effect of dietary ethanol on IOP are rare, and the reported association between alcohol consumption and glaucoma progression may owe, in part, to its neurotoxic effect 44,45 . A single case study describes a systematic transient reduction in IOP following the consumption of Champagne wine in a 66-year-old glaucoma patient 46 .…”
Section: Discussionmentioning
confidence: 99%
“…The individuals were divided by education into four groups: elementary school, middle school, high school, and college and above. Current smoking was defined as participants who smoked >100 cigarettes in their lifetime and current smokers [12]. High-risk alcohol consumption was defined as the consumption of more than 14 drinks per week for men and 10 drinks per week for women [11].…”
Section: Covariatesmentioning
confidence: 99%